Ecosystem Factors that Affecting Chinese Students’ Decision to Enter Higher Education: Ecosystem Factors that Affecting Chinese Students’ Decision to Enter Higher Education - Somboon, Pattamaporn; Kumhom, Naitawan (RATANABUTH JOURNAL, 2025)
The objectives of this research were to 1) study the factors of the educational ecosystem affecting Chinese students pursuing higher education, 2) examine the decision-making processes of Chinese students in choosing higher education, and 3) investigate how the educational ecosystem influences their decisions. This study utilized a quantitative research approach. The sample group consisted of 400 Chinese students currently enrolled in higher education at public and private universities in Bangkok and surrounding areas. The research instrument was a questionnaire. Data analysis included descriptive statistics such as frequency distribution, percentage, mean, and standard deviation, processed using statistical software. The findings revealed that: 1) The factors of the educational ecosystem included the physical environment, cost-related aspects, and personnel. 2) Decision-making regarding pursuing higher education was influenced by expectations and values related to personnel, with positive expectations having a significant impact. 3) The educational ecosystem’s factors, especially personnel-related values, positively influenced the decision-making of Chinese students in higher education.